ESTIMASI VALIDITAS DAN RESPON SISWA TERHADAP BAHAN AJAR MULTI REPRESENTASI : DEFINITIF, MAKROSKOPIS, MIKROSKOPIS, SIMBOLIK PADA MATERI ASAM BASA - Cahya Wulandari; Endang Susilaningsih; K Kasmui (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2018)
This research aims to develop multi-representation teaching material that includes definitive,macroscopic, microscopic, and valid symbolic to determine students’ responses through multi-representation material. This research was conducted at SMA Negeri 1 Karangtengah, with subjects in class XI IPA 3. This research was applied to acid-base materials. The data obtained in this research are the results of expert validation and students’ responses tomulti-representation media teaching material: definitive, macroscopic, microscopic, and symbolic. The data retrieval was conducted by expert judgement method to determine the validity of teaching materials, and the questionnaire method to determine student response through multi-representation material: definitive, macroscopic, microscopic, symbolic was validated by three validators. The research outcome shows that multi-representation media: definitive, macroscopic, microscopic, symbolic valid with an average score of 62 from a total score of 75. The student responses through multi-representation material showed a positive response through the material.